Progressing towards incoherence: Development discourse since the 1980s - Ziai, Aram (Momentum Quarterly, 2014)
From the perspective of archaeological discourse analysis, certain rules can be identified according to which the objects, concepts, subject positions and strategies of development discourse have been formed from the 1950s to the 1970s. Since the ‘crisis of development’ in the 1980s, a number of new concepts have gained prominence in development policy which highlight new aspects: ‘participation’ and ‘ownership’ and ‘sustainable development’ are among the best known. The article argues that this ‘progress’ in the ‘development of development policy’ leads to incoherencies and contradictions, as certain implications of the new concepts are incompatible with some rules of formation which constitute the discourse.